Duality Relations of Fractional Order Transforms (International Journal of Scientific Research in Science and Technology, 2025)
The authors of the article discussed the duality relations of fractional Laplace transforms with kamal, Laplace-Carson, Aboodh, Sumudu, Elazaki, Mohand, Sawi, and natural transforms of fractional orders in this article. Tabular Presentation of Laplace Transforms, Laplace-Carson Transforms, Aboodh Transforms, Sumudu Transforms, Natural Transforms, Elazaki Transforms, Mohand and Sawi Transforms of Fractional Orders of Some Basic Mathematical Functions.